2021
DOI: 10.14814/phy2.14789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanistic/mammalian target of rapamycin complex 1 on mitochondrial dynamics during skeletal muscle hypertrophy

Abstract: Mechanistic/mammalian target of rapamycin (mTOR) is a central factor of protein synthesis signaling and plays an important role in the resistance training‐induced increase in skeletal muscle mass and subsequent skeletal muscle hypertrophy response. In particular, mTOR complex 1 (mTORC1) promotes protein synthesis in ribosomes by activating the downstream effectors, p70S6K and 4EBP1, in skeletal muscle and is highly sensitive to rapamycin, an mTOR inhibitor. Recently, resistance training has also been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…This in vivo model induces compensatory hypertrophy growth of the plantaris muscle through mechanical overload resulting from the surgical removal of the tendons from the synergist muscles (gastrocnemius and soleus), and is very useful as a model to observe exercise-induced muscle hypertrophy and protein synthesis. Consistent with previous reports (Miyazaki et al, 2011;Moriya & Miyazaki, 2018;Shirai, Obara, & Takemasa, 2020;Uemichi et al, 2021), 14 days of mechanical overload induced 25%-50% muscle hypertrophy and enhanced protein synthesis with activated mTOR signaling in mouse skeletal muscle.…”
Section: Experiments 2: Effects Of Lactate Administration By Acute El...supporting
confidence: 93%
See 2 more Smart Citations
“…This in vivo model induces compensatory hypertrophy growth of the plantaris muscle through mechanical overload resulting from the surgical removal of the tendons from the synergist muscles (gastrocnemius and soleus), and is very useful as a model to observe exercise-induced muscle hypertrophy and protein synthesis. Consistent with previous reports (Miyazaki et al, 2011;Moriya & Miyazaki, 2018;Shirai, Obara, & Takemasa, 2020;Uemichi et al, 2021), 14 days of mechanical overload induced 25%-50% muscle hypertrophy and enhanced protein synthesis with activated mTOR signaling in mouse skeletal muscle.…”
Section: Experiments 2: Effects Of Lactate Administration By Acute El...supporting
confidence: 93%
“…We performed lateral synergist ablation surgeries, as previously described, (Shirai, Obara, & Takemasa, 2020 ; Uemichi et al, 2021 ) under anesthesia with 2.0% isoflurane air inhalation. This in vivo model induces hypertrophy of the plantaris muscle by mechanical overload (OL), through the surgical removal of synergist muscles (gastrocnemius and soleus) and is very useful as a model to observe exercise‐induced muscle hypertrophy and protein synthesis (Moriya & Miyazaki, 2018 ; Uemichi et al, 2021 ). One of the characteristics of the plantaris muscles used in this experiment is that the type IIA or IIB fibers are dominant (Miyazaki et al, 2004 ; Souza et al, 2014 ).…”
Section: Materials Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle mass is regulated by the balance of protein synthesis and breakdown. Mammalian/mechanistic target of rapamycin (mTOR) signaling plays an important role in the maintenance of skeletal muscle mass ( Bodine et al, 2001 ; Uemichi et al, 2021 ). It has been demonstrated that this signaling pathway is activated by overload stimuli such as resistance exercise and the intake of amino acids ( Damas et al, 2016 ; Dickinson et al, 2011 ; Shirai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to our suggestion, the increase in the mass of muscle filaments due to overload was not associated with a similar increase in mitochondrial mass, this could lead to this result. Indeed, a recent paper reports that 14 days of functional overload increased the levels of proteins, which regulate mitochondrial fusion and decreased fission controlling proteins, and this could explain the relative reduction in mitochondrial proteins [ 26 ].…”
Section: Discussionmentioning
confidence: 99%